Common fixed point results in uniformly convex metric spaces - Narawadee Nanan (2018)
We obtain some common fixed point results in uniformly convex metric spaces. Our results improve and extend some results of Laowang and Panyanak [W. Laowang, B. Panyanak, A note on common fixed point results in uniformly convex hyperbolic spaces, J. Math., Vol. 2013 (2013), Article ID 503731, 5 pages] and Itoh and Takahashi [S. Itoh, W. Takahashi, The common fixed point theory of singlevalued mappings and multivalued mappings, Pacific J. Math. 79 (1978) 493-508] . © 2014 by the Mathematical Association of Thailand. All rights reserved.